7-O-tyrosyl Silybin Derivatives as a Novel Set of Anti-Prostate Cancer Compounds - Valeria Romanucci; Rita Pagano; Kushal Kandhari; Armando Zarrelli; Maria Petrone; Chapla Agarwal; Rajesh Agarwal; Giovanni Di Fabio (MDPI AG, 2024)
Silybin is a natural compound extensively studied for its hepatoprotective, neuroprotective and anticancer properties. Envisioning the enhancement of silybin potential by suitable modifications in its chemical structure, here, a series of new 7-O-alkyl silybins derivatives were synthesized by the Mitsunobu reaction starting from the silybins and tyrosol-based phenols, such as tyrosol (TYR, 3), 3-methoxytyrosol (MTYR, 4), and 3-hydroxytyrosol (HTYR, 5). This research sought to explore the antioxidant and anticancer properties of eighteen new derivatives and their mechanisms. In particular, the antioxidant properties of new derivatives outlined by the DPPH assay showed a very pronounced activity depending on the tyrosyl moiety (HTYR > MTYR >> TYR). A significant contribution of the HTYR moiety was observed for silybins and 2,3-dehydro-silybin-based derivatives. According to the very potent antioxidant activity, 2,3-dehydro-silybin derivatives 15ab, 15a, and 15b exerted the most potent anticancer activity in human prostate cancer PC-3 cells. Furthermore, flow cytometric analysis for cell cycle and apoptosis revealed that 15ab, 15a, and 15b induce strong G1 phase arrest and increase late apoptotic population in PC-3 cells. Additionally, Western blotting for apoptotic marker cleaved caspase-3 confirmed apoptosis induction by these silybin derivatives in PC-3 cells. These findings hold significant importance in the investigation of anticancer properties of silybin derivatives and strongly encourage swift investigation in pre-clinical models and clinical trials.